The women who have governed in bogota: city, agendas and genre matters (2009)
This essay presents some of the most relevant results of a research carried out about women who occupied decision making positions in the public administration of Bogota between 1992 and 2004. In this study the composition by sex of the government teams and second level positions was established. Even though the socio-demographic, educational and labor profiles of 567 women were reconstructed (including the consultants) and the global public agendas were examined, here we are going to center around the women who have directed the most important entities of the Capital District and that along with the mayors have leaded the city’s transformation. The following were the objectives which guided this work: to analyze the composition by sex at first and second decision making levels, to explain the high female presence in government cabinets, to find out if women and genre matters were present in public agendas, to establish if there was an all female “critical mass” in favor of their own interests and to account for the influence of international cooperation in the development of women and genre policies. With such purpose, an ample revision of political documents, appointment acts and curriculum vitas was carried out. 31 women were interviewed, 27 of whom worked in first level management positions in the above referred period and under two of the five mayors.